(untitled) (The Conference Hub, 2025)
The global march towards Central Bank Digital Currencies (CBDCs) has accelerated, with numerous nations now in advanced pilot or launch stages. For the Republic of Uzbekistan, a nation demonstrating robust economic growth and a strong commitment to digital transformation, the strategic implementation of a CBDC the “Digital Sum” is a critical next step. This thesis constructs a comprehensive, evidence-based framework for a retail CBDC tailored to Uzbekistan’s contemporary economic landscape. Analyzing the latest data from 2024-2025, the research highlights how a CBDC can directly address the persistent shadow economy1, enhance a financial inclusion rate that has improved but still has gaps, and modernize a payment system undergoing rapid change. By evaluating the most recent lessons from global pioneers like China’s e-CNY, India’s digital rupee, and the Eastern Caribbean DCash, this thesis proposes a specific two-tier, hybrid CBDC model. The study concludes that a carefully designed Digital Sum, implemented through a phased roadmap, can serve as a powerful catalyst for financial formalization, monetary policy innovation, and sustainable, inclusive economic growth in Uzbekistan.